Determination of Elastic Moduli for the Geotechnical Site Characterization Using Compressional and Shear Seismic Refraction Tomography at the Proposed Site for Baba Gur-Gur University, Northeastern Kirkuk, Iraq (Iraqi National Journal of Earth Science (INJES), 2025)
2400 m/s and Vs >1100 m/s is considered the sandstone of the Mukdadiya Formation. According to the information provided, the 3rd and 4th layers are appropriate for the engineering project. The resulting geotechnical properties in the area can be used for the preliminary foundation design of any engineering construction.]]>
Keywords: seismic refraction tomography; shear wave refraction; site characterization; Geotechnics; MASW